2014
DOI: 10.5089/9781498382458.005
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Multipliers: Size, Determinants, and Use in Macroeconomic Projections

Abstract: This note * addresses the following issues: • What are fiscal multipliers? • Why are multipliers important for macroeconomic projections and policy design? • What do we know about the size and persistence of multipliers? • What are the determinants of multipliers? • In countries where data availability limits the scope for empirical research, how to come up with multiplier estimates? • How to incorporate multipliers in macroeconomic projections? 1 This note refers to multipliers as one-year multipliers unless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(122 citation statements)
references
References 44 publications
4
105
1
2
Order By: Relevance
“…A growing empirical consensus points to a positive multiplier effect of expansionary fiscal policy (Blanchard/Leigh 2013;Batini et al 2014). Furthermore, traditional Keynesian theory, as well as more recent empirical evidence (Auerbach/Gorodnichenko 2012;Fazzari et al 2015), emphasizes the point-in-business-cycle dependence of fiscal multipliers.…”
Section: Stabilization Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing empirical consensus points to a positive multiplier effect of expansionary fiscal policy (Blanchard/Leigh 2013;Batini et al 2014). Furthermore, traditional Keynesian theory, as well as more recent empirical evidence (Auerbach/Gorodnichenko 2012;Fazzari et al 2015), emphasizes the point-in-business-cycle dependence of fiscal multipliers.…”
Section: Stabilization Propertiesmentioning
confidence: 99%
“…Following the recent empirical literature on multipliers, we differentiate the magnitude of fiscal multipliers in expansions and contractions, and apply multipliers ranging from 0 to 1 for expansions, and 1 to 2.5 for contractions (Batini et al 2014). We then derive subsequent years' GDP figures using ex-ante GDP growth rates and repeating the GDP adjustment procedure, based on the following year's transfer and the relevant multiplier.…”
mentioning
confidence: 99%
“…Keynesians, on the one hand, believe that increases in government expenditure are expected to contribute directly to aggregate demand, whilst decreases in tax are presumed to stimulate private demand indirectly, by adding to the disposable income of the private sector. This means that tax cuts are less potent than spending increases in stimulating the economy, since households may save a significant portion of the additional after tax-income (Batini et al, 2014). The Keynesian theory, moreover, argues that increasing government spending without raising taxes, or reducing tax revenues without cutting expenditure, will stimulate the total demand.…”
Section: Fiscal Multiplier and Its Determinantsmentioning
confidence: 99%
“…Cogan et al (2009), found that the tax multiplier is about -0.3 whilst the spending multiplier is about 0.63. A more complete study of the size of fiscal multipliers in the literature can be found in Spilimbergo, Symansky, and Schindler (2009) and Batini et al (2014).…”
Section: Journal Of Indonesian Economy and Business Septembermentioning
confidence: 99%
See 1 more Smart Citation